Sifat Dan Morfologi Wood Plastic Composite Berbasis Pelepah Sawit/Polietilen Dengan Kompatibiliser Maleic Anhydride Dan Inisiator Benzoil Peroksida - Wahyu Suci Rahmani; Irdoni Irdoni; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The low compatibility between thermoplastic and wood components is a major problem in the manufacture of wood plastic composite. Compatibilities used such as maleic anhydride is useful to increase the value of the mechanical and physical properties of the WPC. The purpose of this study is to determine the effect of the composition palm frond/polyethyleneand maleic anhydride on the properties and morphology of wood plastic composite. The composition of palm frond/polyethylene used is 50/50, 60/40, 70/30 with a mixture of 2% paraffin additive, maleic anhydride (MAH) 3%, 4%, 5%, and benzoyl peroxide 1% of the weight of MAH. The process of mixing fillers, matrices, and additives uses an Internal MixerLabo Plastomill at temperature of 145oC and rotor speed of 80 rpm. The sample was then pressed using a hot press at a temperature of 145oC and a pressure of 100 kgf/cm2. Composites produced were tested including characterization of functional groups, morphological conditions, physical properties and mechanical properties. The results showed that the addition of filler and maleic anhydride composition had a relatively significant effect. The best WPC material is found in the variation palm frond/polyethylene60/40 and MAH 5% with a density value of 1.19 gr/cm3, water content of 0.16%, water absorption capacity of 0.41%, swelling thickness of 0.11%, tensile strength of 18.664 MPa, elastic modulus of 2175.9 MPa, and flexural strength of 35.05 MPa.Keywords: benzoyl peroxide, maleic anhydride, palm stem, wood plastic composite